Analysis of Cadre Understanding of Administrative Procedures and Technology Mastery in Improving Posyandu Reporting Efficiency - Isma Dewita; Dwi Haryono; Sri Utami Rizta (Journal of Applied Business and Technology, 2026)
Posyandu is a community health service that plays an important role in maintaining the health of mothers and children. However, the implementation of administration and data reporting is often hindered by the lack of understanding among cadres, administrative procedures, and low mastery of technology. This study aims to analyze the understanding of Posyandu cadres, administrative procedures, and technology mastery in improving reporting efficiency. The study uses a quantitative descriptive approach with a questionnaire as the main instrument, involving Posyandu cadres. The sampling technique used is Convenience Sampling, where respondents are selected based on who is willing or who fills out the questionnaire, with a total of 68 cadres. Data analysis to test the hypothesis uses Path Analysis with SPSS version 30 application program. The results of the analysis show that the hypothesis of cadre understanding (X1), administrative procedures (X2), and technology mastery (X3) has an influence on improving reporting efficiency (Y) both simultaneously and partially. The results of testing all variables are accepted because the path coefficients of X1, X2, and X3 against Y are significant. The results of the path determination coefficient are 0.449 or 44,9%.